Perceptions of the need for minority languages by nurses in Southern Taiwan. (26th November 2018) - Tsai, Mei-Hui; Lee, Huan-Fang; Jeng, Shuen-Lin; Lin, Sheng-Che; Hsieh, Li-Wei; Chuang, Jen-Pin; Jacobs, Elizabeth
Abstract : Background: While language barriers between healthcare providers and minority-language-speaking patients often lead to miscommunication and jeopardize patient safety, language audits of the former have received little attention. Goal: Based on the context in Southern Taiwan, where the elderly population mainly speaks the local dialect Taiwanese, this study examines nurses' perceptions of their proficiency in and need for medical Taiwanese ('MED-TW'), and attitudes toward it. Method: A questionnaire survey was conducted among 859 nurses from three levels of healthcare units: primary care stations (H1), a regional hospital (H2) and a medical center (H3). Results: Nurses from the rural-based H1 unit displayed significantly stronger needs for Taiwanese (TW) than those from urban-based H2 and H3. Specifically, H1 nurses reported encounters with the largest proportion of TW-speaking clients (p<0.001) and the highest frequency of using TW with clients (p<0.001). However, H1 nurses' self-evaluation of their TW proficiency revealed a lower score than those of the H2 and H3 nurses, especially with regard to medical TW proficiency (p<0.05). Finally, while nurses with a high command of TW felt it helped their work, those with a low level did not feel this impacted their performance. Conclusion: Nurses working in locations where the use of the minority language is prevalent would benefit more from learning this language.